Role of miR-16, 146a, 19b and 720 gene expressions in the pathogenesis and diagnosis of vitiligo - Olfat G. Shaker; Talal A. Abd elrahim; Somia Azzam; Mai Mohamed El-Zook; Nesreen M. Aboraia (Scientific Reports)
Abstract Vitiligo is a common long-term depigmenting skin disorder that is characterized by patches of skin losing their pigment. To evaluate serum/tissue levels of miR-16, 146a, 19b and 720 in vitiligo patients and healthy controls, also analyzing the correlations between all biomarkers to indicate whether those can be used to early diagnose vitiligo patients. Forty-subjects were included, divided into two equal groups, 20 healthy matched individuals and 20 vitiligo patients. For all groups a 5 mL venous blood sample for serum isolation was taken and analyzed for the serum level of miRNAs. For tissue analysis, 3 mm biopsy was taken. For all patients Vitiligo area scoring index (VASI), vitiligo disease activity (VIDA), disease duration and extent percentages were calculated. No significant difference was observed in age and sex ratio among the two groups (p > 0.05). Serum, expression levels for miR-16, 146a, and 19b were overexpressed in vitiligo patients as compared to healthy controls with p-value 0.000 for all biomarkers. While miR-720 was reported low in vitiligo patients compared to controls (p = 0.000). For tissue samples, miR-16, 146a, 19b were overexpressed in vitiligo patients with p-values 0.000, 0.000 and < 0.001 respectively, while for the expression level of miR-720 in tissue, the level was low compared to controls (p = 0.000). There are positive correlations between VASI and miR-16, 146a in serum and miR-146a in tissue. Also positive correlations between disease extent and both miR-16 and miR-146a in serum and in tissue was found. A negative correlation between VIDA and miR-720 in serum was found. Various correlations between the selected miRNAs were reported. Based upon the expression levels of miR-16, 146a, 19b and 720 in both serum and tissue, these biomarkers can be used as early indicators for vitiligo.